2014
DOI: 10.3109/17453674.2014.991629
|View full text |Cite
|
Sign up to set email alerts
|

Doubtful effect of continuous intraarticular analgesia after total knee arthroplasty

Abstract: Background and purposeLocal infiltration analgesia (LIA) is well established for effective postoperative pain relief in total knee arthroplasty (TKA). To prolong the effect of LIA, infusion pumps with local intraarticular analgesia can be used. We evaluated the effect of such an infusion pump for the first 48 h postoperatively regarding pain, knee function, length of stay (LOS) in hospital, and complications.Patients and methods200 patients received peroperative LIA and a continuous intraarticular elastomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
0
32
1
4
Order By: Relevance
“…The most effective technique consisted of infiltrating a mixture of high-dose ropivacaine with adrenaline and ketorolac. 10 Single intra-articular versus continuous perfusion were also studied, 19 but no differences were observed between these two techniques. A single LIA intraoperative injection seems to be the most effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective technique consisted of infiltrating a mixture of high-dose ropivacaine with adrenaline and ketorolac. 10 Single intra-articular versus continuous perfusion were also studied, 19 but no differences were observed between these two techniques. A single LIA intraoperative injection seems to be the most effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some major complications for this method, which are wound infection and local anesthetic toxicity. In the study of Ali et al, continuous LIA appeared to have no significant effect on postoperative pain and a higher rate of wound-healing complications and deep wound infections occurred [20].…”
Section: Discussionmentioning
confidence: 87%
“…It has to be noted that studies discussed here used higher doses of local anesthetic and it has been combined with other analgesic drugs. Furthermore, the continuous method was widely used for administration of LIA [11,14,20,21]. Ropivacaine is a long-acting local anesthetic and has less cardiac toxicity than bupivacaine, but when using high doses it suppresses the central nervous and cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…After reading the titles and abstracts, 49 studies were excluded according to the inclusion criteria. Finally, 7 RCTs [1018] with 587 TKAs were identified in our study (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al [11] conducted a RCT and found that pain score and morphine consumption are not significantly reduced when adding 48 h of 0.5% bupivacaine infiltration with pain pump. Ali et al [18] also performed a RCT about CLIA with placebo for pain control after TKA and found that CLIA has no relevant clinical effect on VAS pain and does not affect LOS, morphine consumption but with a higher risk of wound-healing complications: deep infections. In this meta-analysis, the pain score was reduced 11.09 score with rest at 24 h and 13.94 score at 24 h with mobilization.…”
Section: Discussionmentioning
confidence: 99%